A Behind‐the‐Scenes Guide to School‐Based Research. Issue 1 (March 2014) - Plummer, Benjamin D.; Galla, Brian M.; Finn, Amy S.; Patrick, Sarah D.; Meketon, David; Leonard, Julia; Goetz, Calvin; Fernandez‐Vina, Elizabeth; Bartolino, Sara; White, Rachel E.; Duckworth, Angela L.
ABSTRACT Schools are an important context for both basic and applied scientific research. Unlike the laboratory, however, the physical and social conditions of schools are not under the exclusive control of scientists. In this article, we liken collecting data in schools to putting on a theatrical production. We begin by describing the large cast of characters whose collaborative efforts make school‐based research possible. Next, we address the critics, including the university Institutional Review Board (IRB) and school administrators, whose feedback often improves the final study design. We then turn our attention to set building, stage directions, and rehearsals—key steps in the iterative process of refining study procedures. We end with a discussion of the day of data collection itself and activities that take place after the curtain drops. Throughout, we make recommendations based on our recent experience collecting data at several high schools.